(untitled) (International journal of medical sciences, 2025)
This article provides an extensive scientific review of the types of antibiotics, their mechanisms of action, pharmacological properties, and the scientific basis of antibiotic resistance. The adaptation mechanisms of microorganisms to antibiotics, mutation processes, formation of genetic resistance, and its impact on the global healthcare system are thoroughly analyzed. The emergence of resistant bacterial strains due to improper use of antibiotics, methods to combat resistance, and modern solutions are discussed based on theoretical and scientific approaches.